Health-related quality of life in populations with diabetes, prediabetes, and normal glycemic levels in Guangzhou, China: a cross-sectional study - Li, Meichen; Liu, Na; Jiang, Guli; Zeng, Hongli; Guo, Jianwen; Wu, Darong; Zhou, Hui; Wen, Zehuai; Zhou, Li (Frontiers in Endocrinology, 2025)
BackgroundThe association of prediabetes and diabetes on health-related quality of life (HRQoL) remains inconclusive in current epidemiological research. In this investigation, we administered 5-level EuroQoL-5 dimension version (EQ-5D-5L) to systematically assess HRQoL across glycemic strata (diabetes, prediabetes, and normal glycemic levels) in Guangzhou, and to offer baseline data that can be easily compared to other regions in China or across countries.MethodThis investigation utilized baseline cross-sectional data extracted from a three-year prospective cohort study conducted at the Health Management Center of Guangzhou 11th People’s Hospital. Propensity score matching was implemented at a 1:1:4 ratio to balance participants across diabetes, prediabetes, and normal glycemic group. HRQoL outcomes, operationalized through EQ-Index and EQ visual analog scale (EQ-VAS) measurements, were compared across groups using one-way ANOVA or Wilcoxon rank-sum tests. Multivariate linear regression was constructed to adjust for potential confounders, followed by subgroup analyses stratified by sex, age categories, body mass index (BMI) classifications, and hypertension comorbidity status.ResultsA total of 18,605 participants were included in the study. After propensity score matching, 533 participants allocated to the prediabetes group, 533 to the diabetes group, and 2064 to the normal glycemic group. Intergroup comparisons demonstrated significantly lower EQ-VAS scores in the diabetes group (79.11) compared to both prediabetes (80.67) and normal glycemic group (81.65). Similarly, the diabetes group exhibited the lowest EQ-Index scores (0.968) relative to prediabetes (0.972) and normal glycemic group (0.972). Multivariate linear regression adjusted with sex, age, BMI, etc. revealed a 2.139-point reduction in EQ-VAS scores for the diabetes group versus normal glycemic group (95% CI: -3.748, -0.530; P=0.009). Subgroup analyses identified particularly compromised HRQoL in diabetes and prediabetes populations among female participants, individuals with obesity, and those aged ≥60 years.DiscussionPrediabetes and diabetes mellitus are associated with diminished HRQoL compared to normal glycemic levels, with a more pronounced negative associations observed among female populations, older adults, and individuals with obesity. These findings emphasize the clinical necessity for implementing targeted interventions to optimize HRQoL outcomes in these high-risk subgroups, which aligns with the fundamental objectives of contemporary diabetes management frameworks.Clinical trial registrationClinicalTrials.gov ID: NCT05315895.